Belief about the self a defense of the property theory of content - Feit, Neil. (Oxford : Oxford University Press, 2008)
Philosophers typically suppose that the contents of our beliefs and other cognitive attitudes are propositions - things that might be true or false, and their truth values do not vary from time to time, place to place, or person to person. Neil Feit argues that this view breaks down in the face of beliefs about the self.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Self (Philosophy)